1996
DOI: 10.1159/000217297
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Buflomedil On The Neutrophil-Endothelial Cell Interaction Under Inflammatory And Hypoxia Conditions

Abstract: In hypoxia/ischaemia and ischaemia/reperfusion, human neurophils are likely to play an important role in the development of endothehal cell damage in the microcirculation. Buflomedil hypochloride improves the capillary perfusion in such related situations, evoking a possible effect upon neutrophils. Using in vitro models of cell adhesion, buflomedil decreased 100% of histamin related neutrophil adhesion (flow sytem) and partially inhibited adhesion after IL-1–4 hours (flow and stable systems). Hypoxia induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Recently, Capecchi and coworkers [30] reported that buflomedil infusion increases plasma levels of adenosine and adenine nucleotides in humans, very likely through an enhanced release (rather than a cell uptake inhibition) of adenosine. Moreover, Boisseau and coworkers [4] demonstrated that the buflomedil-induced reduction in neutrophil adhesion following hypoxia is very likely mediated by activation of the A 2 receptor. Adenosine has been shown to be a sensitive indicator of cerebral ischemia and a modulator of cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Capecchi and coworkers [30] reported that buflomedil infusion increases plasma levels of adenosine and adenine nucleotides in humans, very likely through an enhanced release (rather than a cell uptake inhibition) of adenosine. Moreover, Boisseau and coworkers [4] demonstrated that the buflomedil-induced reduction in neutrophil adhesion following hypoxia is very likely mediated by activation of the A 2 receptor. Adenosine has been shown to be a sensitive indicator of cerebral ischemia and a modulator of cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies on human neutrophils showed that buflomedil reduces aggregation, pseudopod formation, adhesion and degranulation of lisosomial enzymes. Boisseau and coworkers [4] report that buflomedil reduces hypoxia-induced neutrophil adhesion and P-selectin expression at the endothelial cell surface, suggesting that the drug acts through the A 2 receptor. Moreover, in a porcine model of hyperdynamic endotoxemia, buflomedil proved to be able to suppress systemic activation of circulating and emigrated polymorphonuclear leukocytes [5].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of therapeutic regimes have therefore been investigated in experimental and clinical settings for improvement of microvascular perfusion and acceleration of wound healing [3,4,5,6,7,8,9]. Buflomedil hydrochloride has been shown to ameliorate microcirculation, probably due to its vasodilatory and rheological properties [10,11,12,13] and, consequently, wound healing [14]. However, oral and parenteral application of drugs can be accompanied by the risk of serious side effects or the disadvantage of early inactivation of the drug.…”
Section: Introductionmentioning
confidence: 99%